The long-term relationship between economic development and regional inequality: South-West Europe, 1860-2010 - Alfonso Díez-Minguela; Rafael González-Val; Julio Martinez-Galarraga; M. Teresa Sanchis; Daniel A. Tirado (European Historical Economics Society (EHES), 2017)
This paper analyses the long-term relationship between regional inequality and economic development. Our data set includes information on national and regional per-capita GDP for four countries: France, Italy, Portugal and Spain. Data are compiled on a decadal basis for the period 1860-2010, thus enabling the evolution of regional inequalities throughout the whole process of economic development to be examined. Using parametric and semiparametric regressions, our results confirm the rise and fall of regional inequalities over time, i.e. the existence of an inverted-U curve since the early stages of modern economic growth, as the Williamson hypothesis suggests. We also find evidence that, in recent decades, regional inequalities have been on the rise again. As a result, the long-term relationship between national economic development and spatial inequalities describes an elephant-shaped curve.
Keywords: N9; O18; R1; 330; Economic development; regional inequalities; Kuznets curve; Europe; economic history